Use of carbon fiber to enchance the physical and mechanical properties of particle board - Vigneswaran, Rajamohan (2014)
Particle board which well known as an engineered wood product manufactured or produced from wood chips, sawmill shavings, or even saw dust, and a synthetic resin or other suitable binder, which is pressed and extruded. These boards becoming less popular in market due to low physical and mechanical strength. This research is on increasing the mechanical and physical property of particle board by using carbon nano fiber as filler. The carbon nano fiber has the ability to increase mechanical properties of particle boards. The main objective of this research is to enhance the mechanical properties of the wood composite boards. The carbon nano fiber were used in the production of particle boards. The different percentage of carbon nano fiber was used for comparing the results for the mechanical strenght. The result shows that, adding carbon nano fiber as filler had improved the MOR, IB and reduce thickness swelling values, as compared to standard board. So, it proved that the carbon nano fiber can improve the thermal and mechanical properties of wood composites. The present of carbon nano fiber reduce the formaldehyde emission and increase the curing rate and also thermal stability is proven by the DSC and TGA analysis. As a conclusion, the improvement of mechanical properties of wood composites will increase the demand of Malaysian Particle Board in global market and also reduce the cost of production.